The Astral Procreation: Myth versus Reality? - Tatar, Maria Magdolna (Acta Mongolica, 2002)
In this paper I intend to deal with a wide-spread myth, known among the Mongols and Turks, from a different, less mythographic, more sociohistorical point of view